Transcranial direct current stimulation and sports performance - Edwards, D. J.; Cortes, M.; Wortman-Jutt, S.; Putrino, D.; Bikson, M.; Thickbroom, G.; Pascual-Leone, A. (Frontiers in Human Neuroscience, 2017)
The application of transcranial direct current stimulation (tDCS) has moved from the laboratory to the wider community. This form of non-invasive brain stimulation has been shown in a number of controlled animal and human experiments, over nearly five decades, to modulate brain physiology, cognitive functions, and behavior. While its effects are variable across and within individuals, it is not unreasonable to state that tDCS harbors the potential to enhance executive and physical human performance. In a society increasingly driven to succeed with less effort, performance enhancement with an intervention that has an excellent safety record, is well tolerated, relatively inexpensive and readily available, is particularly appealing. Here, we offer a perspective on tDCS for the enhancement of physical performance in sport. The ethical and legal implications of the transition of tDCS from academic experimental work to general-public use, are discussed elsewhere (Janssens and Kraft, 2012; Bain et al., 2015; Fregni et al., 2015; Bikson et al., 2016a; Kuersten and Hamilton, 2016; Zettler, 2016).